Integrative taxonomy supports high species diversity of south-eastern Brazilian mountain catfishes of the T. reinhardti group (Siluriformes: Trichomycteridae). Issue 6 (18th August 2021) - Costa, Wilson J. E. M.; Katz, Axel M.
Abstract : The mountain area between the Mantiqueira and Espinhaço ranges of south-eastern Brazil is of special interest for biologists by sheltering headwaters of two of the largest South American river basins, as well as comprising sections of two main world biodiversity hotspots. Mineral exploitation activities have caused great environmental impact, but biological inventories have demonstrated a rich biota with some organisms still poorly known. We herein analyse catfishes of the Trichomycterus reinhardti species group, endemic to this area. With the objective of inferring species limits, we combine morphological variation to unilocus coalescent methods of species delimitation using fragments of the mitochondrial genome (total of 1924 bp) for 38 individuals collected in 14 sites. The phylogenetic analysis supported a clade endemic to the Rio São Francisco basin and neighbouring Rio Doce headwaters, Espinhaço mountain range, and another one, endemic to the Rio Grande drainage, Rio Paraná basin, between Mantiqueira and Canastra mountain ranges. This biogeographic pattern may be explained by geological evidence indicating that the upper Rio Grande drainage was connected to the upper Rio São Francisco basin until the Middle Miocene, instead of being part of the Rio Paraná basin as today. The integrative analysis supported a total of 10 species, six of which are new and here described. Interestingly, the small areas inhabited by species here delimited are highly coincident with the distribution range of other mountain fish species. High level of local species endemism is possibly related to the uncommon regional relief, with small subdrainages crossed by transversal hills as a result of geological gaps, supporting a complex palaeogeographic scenario favouring isolation of taxa in small areas. Under a conservation perspective, these small areas of endemism for mountain fishes deserve special attention due to the process of environmental decline along centuries in the region. http://www.zoobank.org/urn:lsid:zoobank.org:pub:0E3981E9-D7A9-4C9B-B56A-85621F33A7CB